PEMBERDAYAAN WANITA PEDAGANG SEKTOR INFORMAL DALAM PENINGKATAN PENDAPATAN RUMAH TANGGA - Salamatun Asakdiyah (Universitas Ahmad Dahlan, 2015)
This study aims to determine the level of income of women traders on the domestic kiosk and analyzes the factors that influence the level of income of women traders at the kiosk households in Umbulharjo Gondomanan District and sub-district of Yogyakarta. These factors include venture capital, working hours, and the amount of labor. The test results are individually regression coefficient indicates that the variable amount of venture capital and the amount of labor a significant effect on income levels. While the variable working hours no significant effect on the level of income.